Soil Fungal Community Composition, Not Assembly Process, Was Altered by Nitrogen Addition and Precipitation Changes at an Alpine Steppe - Xiao, Yuanming; Li, Changbin; Yang, Yang; Peng, Yunfeng; Yang, Yuanhe; Zhou, Guoying (Frontiers in Microbiology, 2020)
Soil microbial community assembly processes and underlying drivers have long attracted considerable attention. However, the responses of these processes to nitrogen addition and changes in precipitation are poorly understood, especially in the alpine steppe on the Qinghai-Tibetan Plateau. In this study, we conducted a field manipulative experiment of nitrogen addition and precipitation change in an alpine steppe on the northeastern Qinghai-Tibetan Plateau, and used high-throughput sequencing to investigate the responses of community assemblage mechanisms of soil fungi and the corresponding potential drivers. Soil fungal community compositions were significantly altered under nitrogen addition and precipitation change. OTU richness, Chao 1 index, and Faith’s PD index decreased under nitrogen addition combined with precipitation reduction treatment, whereas the Shannon-Weiner index declined only under precipitation reduction treatment. Phylogenetic clustering of fungal community structures was not significantly altered by both nitrogen addition and precipitation change, indicating that environmental filtering was a dominant ecological process controlling fungal community assemblage and remained constant. Soil pH did not have significant and direct effects on the soil fungal community, whereas soil moisture, soil available nitrogen, and phosphorus content jointly had the strongest influence and direct effect on the fungal community composition in soil. These results suggest that the above three factors may be the dominant drivers structuring fungal communities in the alpine steppe under nitrogen addition and precipitation changes.